Mediação do fonoaudiólogo no processo de capacitação do professor do aluno surdo - Tenor, Ana Cláudia [UNESP] (2014)
The inclusion of deaf students in regular schools has generated discussions and polemics among researchers, professionals and families seeking for a better quality of education for these students. In this context, the education and training of teachers are considered targets to be met. The aim of this study was to systematize actions to train teachers of deaf students by mediation of speech therapists. A father, a mother and two teachers of deaf students from a city inland in São Paulo State have participated in this study. In the first part parents and teachers of these students were interviewed, the adapted Protocol Paula (2007) was applied to assess the communication skills of these student within school environment and observations have been conducted in the classroom. Protocol data and observations were incorporated into the transcripts of the interviews, constituting a single text according to assumptions of data triangulation Triviños (1992). The content analysis was performed according to Bardin (2004), which consisted of thematic units classification. From the themes identified in Part 1, a training program has been developed to involve the family and the teachers. The methodology initially proposed was the focal group, adapting the model used by Ferreira (2006). Due to the lack of adhesion of families the methodological procedure has been modified to training courses in a group, which occurred through discussions with teachers. During the second stage teachers took part in group training, filming, observations and mediations of the researcher also occurred in the classroom. The meetings were recorded and the material was transcribed and then organized into notebooks content. The data from these notebooks, records of observations and recordings were triangulated according to Triviños (1992) generating themes and subthemes analysis. In the third part, opinions about the speech therapist participation in the training program...